Ageing in Two Worlds: Policy and Culture in Pakistan and Hungary - Minahil; Rabia (Magyar Gerontológia, 2025)
Pakistan and Hungary are at different stages of population ageing, yet both face challenges in balancing family caregiving and formal support. This study explores how national ageing policies and cultural attitudes shape elder care in these contexts.